Priming Emotional Salience Reveals the Role of Episodic Memory and Task Conflict in the Non-color Word Stroop Task - Hsieh, Chiao Wei; Sharma, Dinkar (Frontiers in Psychology, 2019)
Previous research attempted to account for the emotional Stroop effect based on connectionist models of the Stroop task that implicate conflict in the output layer as the underlying mechanism (e.g. Williams et al., 1996). Based on Kalanthroff et al.’s (2015) proactive-control/task-conflict (PC-TC) model our study argues that the interference from non-colour words (neutral and negative words) is due to task conflict. Using a study-test procedure 120 participants (59 high and 61 low trait anxiety) studied negative and neutral control words prior to being tested on a colour responding task that included studied and unstudied words. The results for the low anxiety group show no emotional Stroop effect but do demonstrate the slowdown in response latencies to a block of studied and unstudied words compared to a block of unstudied words. In contrast, the high anxiety group shows (a) an emotional Stroop effect but only for studied negative words and (b) a reversed sequential modulation in which studied negative words slowed down the colour-responding of studied negative words on the next trial. We consider how these findings can be incorporated into the PC-TC model and suggest the interacting role of trait anxiety, episodic memory and emotional salience driving attention that is based on task conflict.